Heinrich von Kleist Studies in the Character and Meaning of his Writings - Ellis, John M. (UNC Studies in the Germanic Languages and Literatures, 1979)
Ellis's book confronts directly the most central issue of Kleist criticism: the essential nature and meaning of his work. Rather than provide a general survey of Kleist's writings, Ellis performs an analysis of six of his most mature works: "Der Findling", "Die Marquise von O. . .", "Das Erdbeben in Chili", "Der Zweitkampf", "Michael Kohlhaas", and "Prinz Friedrich von Homburg". Ellis draws some general conclusions about the uniquely Kleistian character of these six works which are at sharp variance with previous Kleist criticism.